Effect of Intraperitoneal Etanercept on Oxidative Stress in Rats with Peritonitis. (14th March 2016) - Yildirim, Yasar; Cellad, Esma Gulsum; Kara, Ali Veysel; Yilmaz, Zülfükar; Kadiroglu, Ali Kemal; Bahadir, Mehmet Veysi; Gul, Mesut; Ketani, Muzaffer Aydin; Yilmaz, Mehmet Emin
Abstract : Our aim was to evaluate effect of etanercept on oxidative stress parameters in rats with experimental peritonitis and investigate the availability of etanercept usage in the treatment of peritonitis in the future. Twenty-eight rats were divided into four groups as control (group 1), peritonitis (group 2), peritonitis + cefazolin sodium (group 3), and peritonitis + cefazolin sodium + etanercept (group 4). Peritoneal tissue and blood samples were taken from all of the rats for histopathological and biochemical examination. The oxidative stress parameters were examined in blood and tissue samples. It was observed that rats with peritonitis benefit from cefazolin sodium treatment. Evaluating the effectiveness of etanercept was our main objective for this study. In this perspective, we compared group 3 and group 4 and found statistically significant decreases in oxidative parameters and statistically significant increases in antioxidants in serum and tissue samples in group 4. It is observed that there was a significant contribution of etanercept on biochemical and also histopathological results. As a result, the TNF- α inhibitor, etanercept, in addition to antibiotics given in the early treatment of peritonitis results in more significant improvement of histopathological and oxidative parameters as compared to antibiotics alone.